Experimental Investigation of a Gasoline-Charged Heat Pipe Solar Water Heater - Ali J. S. Alrafad; Ali F. Ali Fadiel; Karima A. S. Elhabib (African Journal of Advanced Pure and Applied Sciences, 2023)
An experimental investigation was conducted under actual weather conditions at Higher Institute for Sciences and Technology Altmimi in Libya located at 32.24°N latitude and 23.17°E longitude. The solar complex is designed, manufactured, and assembled with the effect of thermal pipes. The thermal tube is integrated into Flat sucking absorbs heat from solar radiation and this part is considered an evaporator, the other side of the Heat tube is an intense part that is inserted into the water tank, gasoline was selected as a charged work fluid in the copper pipe due to its availability in the local market. Temperatures were measured in the assembly’s absorption board and water temperature in the storage tank and instantaneous efficiency every hour. We noticed that the solar system started heating up the water when it reached a degree. The flat temperature is 80OC, which is the boiling temperature of the gasoline, and the maximum temperature of water reached Instantaneous efficiency is about 46 ° C 23% respectively.